Performance Appraisal and its impact on behavioral and Attitudinal work outcomes Analytical research of the views of a sample of teaching staff at Colleges of the University of Fallujah - Mushier, Ahmed Rajab; Raheemah, Salma Hutyta (Journal of Economics and Administrative Sciences, 2021)
The current research aims to know the extent of the impact of performance evaluation in its dimensions as an explanatory variable in the behavioural and attitudinal work outputs with its dimensions as a response variable in order to reach appropriate solutions through which the University of Fallujah seeks to achieve its goal in the process of diagnosing the axes of strength and to benefit from them in the process of strengthening the status and sobriety of the academic position of the professor and the researcher relied on The descriptive and analytical approach in carrying out this study, and data was collected from university professors, including leaders, heads of departments and divisions, who numbered (97) teachers. And field observations as tools to assist in enhancing the results of the questionnaire. The researcher relied on the (SPSS V.19) program. In processing and analyzing questionnaires, descriptive statistical methods (the arithmetic mean, standard deviation, coefficient of variation, simple linear regression, relative importance, correlation coefficient, Pearson correlation coefficient), while the most prominent results reached by the researcher showed the existence of a correlation relationship and a significant influence Moral significance for performance evaluation in behavioural and attitudinal work outcomes